Efektivitas Sistem Manajemen Bencana Di Indonesia: Studi Kasus Banjir Jakarta - Alwan, Nabil; Saepudin, Eli Apud; Ernawati, Surni; Susilawati, Sindi; Imanda, M. Afan; Hikmatulaila, Enong Ais (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research examines the effectiveness of the disaster management system in Indonesia with a focus on a case study of flooding in Jakarta. Flooding is an annual disaster that often occurs in Jakarta due to high rainfall, poor drainage patterns and land use change. The disaster management system in Indonesia covers various stages, including mitigation, preparedness, response and recovery. However, implementation in the field often faces challenges, such as suboptimal coordination between agencies, budget constraints, and low public awareness. From these findings, it is recommended to increase human resource capacity, strengthen the coordination system between agencies, and increase public awareness and involvement in disaster mitigation and preparedness. In addition, the use of modern technology such as data-based flood mapping and more effective early warning is expected to improve the response to flood disasters. With these efforts, it is hoped that the disaster management system in Jakarta can be more effective in reducing the impact of flooding and protecting public safety.